Pearls of wisdom? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Pearls of wisdom?The October 2000 issue of Tahiti-Pacific Magazine reports on clashes between villagers and the new owner of an oyster pearl farm on the atoll of Penrhyn in the Cook Islands. A recent judgement by the islands High Court had...